PENGARUH PRODUKSI, HARGA DAN LUAS LAHAN TERHADAP PENDAPATAN PETANI CABAI MERAH DI INDONESIA - Mardiah Dabutar; Ratna Husein (LPPM Universitas Malikussaleh - Indonesia, 2022)
This study aims to determine the effect of production, price and land area on the income of red chili farmers in Indonesia. This study uses multiple linear regression to analize observed data . The results of the study showed that partially the production, price and land area have a positive and significant effect on the income of red chili farmers in Indonesia. Based on the result simultaneously shaved that production, price and land area have a positive and significant effect on the income of red chili farmers in Indonesia, the magnitude of the influence has 85% while 15% was influenced by variables outside this model.